CDK5 Regulatory Subunit-Associated Protein 1-Like 1 Gene Polymorphisms and Gestational Diabetes Mellitus Risk: A Trial Sequential Meta-Analysis of 13,306 Subjects - Yu, Xiang-yuan; Song, Li-ping; Wei, Shu-dan; Wen, Xiao-lan; Liu, Da-bin (Frontiers in Endocrinology, 2021)
CDK5 regulatory subunit associated protein 1-like 1(CDKAL1) contributes to islet β-cell function and insulin secretion by inhibiting the activation of CDK5. Current studies on the relationship between CDKAL1 polymorphisms rs7756992 A>G and rs7754840 C>G and the risk of gestational diabetes mellitus (GDM) have drawn contradictory conclusions. A meta-analysis with fixed- or random-effect model was conducted to estimate the correlation between studied CDKAL1 polymorphisms and GDM risk with the summary odds ratio (OR) and 95% confidence interval (CI). Further the trial sequential analysis (TSA) and false positive report probability (FPRP) analysis were performed to confirm the study findings. A total of 13,306 subjects were included in the present study. Meta-analysis results showed that the variant heterozygous and homozygous genotypes of the two polymorphisms were associated with increased GDM risk in comparison to the wild AA genotype (AG vs. AA: OR = 1.23, 95% CI = 1.08, 1.41, P = 0.002; GG vs. AA: OR = 1.47, 95% CI = 1.05, 2.05, P = 0.024 for rs7756992 and CG vs. GG: OR = 1.36, 95% CI = 1.13, 1.65, P = 0.002; CC vs. GG: OR = 1.76, 95% CI = 1.37, 2.26, P < 0.001 for rs7754840). The TSA confirmed a significant association between rs7754840 and the susceptibility to GDM because the cumulative Z-curve crossed both the conventional cutoff value and the TSA boundaries under the heterozygote and homozygote models. This study supported that rs7756992 and rs7754840 were mainly associated with the susceptibility of GDM. However, further functional studies are warranted to clarify the mechanism.